Understanding of Junior High School Students in Banda Aceh City About Traffic Signs, and the Obligation to Have A Driving Permit - Yusrijal Abdar*; Rizal Fahmi; Ridayani Ridayani (Universitas Syiah Kuala, 2021)
The purpose of this study is to describe the understanding of junior high school students in Banda Aceh City about traffic signs and the obligation to have a driving license. The focus of this research: 1). How do students understand about traffic signs. (2) How is the student's understanding of the obligation to have a driver's license for motorists. Research using qualitative descriptive method. The research subjects for junior high school students in Banda Aceh City were 14 students. Research subjects are determined arbitrarily according to research needs. Data collection techniques using free interviews where students can be found. The results of the study used narrative analysis of all interview results through three stages, data reduction, data presentation and drawing conclusions. The results of the study showed that: (1) Banda Aceh Junior High School students' understanding of traffic signs was still low. Many students still do not understand traffic sign symbols. (2) The understanding of junior high school students in Banda Aceh City regarding the obligation to have a SIM in general is good, but students who become their informants say they do not have a SIM, and they are forced to use motorized vehicles for school due to the distance from where they live to school and their parents. permit driving a motorized vehicle to school to make it easier for parents of students to shuttle from home to school and vice versa. This research should be continued with parents regarding education in the family, especially regarding aspects of traffic according to applicable regulations.